China's New Silk Road An Emerging World Order - Carmen Amado Mendes (2019)
Much is being written about China’s new 'One Belt, One Road' initiative, but much of the writing focuses on China itself, on the destinations of the road – Europe and the Middle East – or on the countries through which the road passes, such as Central Asia. This book takes a different approach, assessing the views of East Asian and other countries on the Belt and Road Initiative, both from a transnational and multidisciplinary perspective. The book considers international visions and limitations of the New Silk Road as a new paradigm, explores economic and trade aspects, including infrastructure networks, financial mechanisms, and the likely impact for other countries and regions, and analyses the likely implications for regional and trans-regional cooperation and competition. Western and Asian regional perspectives on the New Silk Road, including from India, Pakistan, Southeast Asia and Japan are considered throughout the book.